Preparation method and application of lithium-sulfur battery catalyst

By using three-dimensional porous graphene and Nb-N-C catalysts in lithium-sulfur batteries, the transformation of LiPSs is accelerated by using local microelectric fields to accelerate the conversion of LiPSs, and the problem of shuttle effect of LiPSs in lithium-sulfur batteries is solved, significantly improving the battery's magnification and cycle stability performance.

CN119327503BActive Publication Date: 2025-02-25HENAN INST OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411873161.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-02-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Due to the poor sulfur conductivity, severe sulfur volume expansion during circulation, and the shuttle effect of the intermediate product lithium polysulfide (LiPSs), lithium sulfur batteries have low capacity, low safety performance and poor circulation stability, which limits their commercial development.

Method used

Using the spatial domain domain effect of three-dimensional porous graphene and based on the iron voltage and electrical effect of Nb-N-C, a local microelectric field is formed in situ, which accelerates the conversion of soluble LiPSs to the insoluble discharge product Li2S, achieving rapid and complete catalysis of LiPSs Conversion.

Benefits of technology

It significantly improves the rate performance and cycle stability of lithium-sulfur batteries, inhibits the shuttle effect of LiPSs, and thus improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327503B_ABST
    Figure CN119327503B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a lithium-sulfur battery catalyst. The method utilizes the spatial confinement effect of three-dimensional porous graphene and forms a local micro-electric field in situ based on the ferroelectric piezoelectric effect of Nb-N-C during the charge and discharge process, thereby accelerating the catalyst to convert soluble LiPSs into insoluble discharge product Li2S, thereby achieving rapid and complete catalytic conversion of LiPSs and significantly improving the rate performance and cycle stability of the lithium-sulfur battery. Therefore, the prepared lithium-sulfur battery catalyst can be used to prepare lithium-sulfur battery positive electrode materials and further assembled into a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a preparation method and application of a lithium-sulfur battery catalyst. Background Art

[0002] Lithium-sulfur batteries have high theoretical energy density (2600Wh / kg) and specific capacity (1675mAh / g), and have broad application prospects in the fields of drones, electric vehicles, and submarines. They are considered to be the most promising next-generation high-energy-density electrochemical energy storage technology. However, problems such as the poor conductivity of sulfur (S) and the discharge product lithium sulfide (Li2S), the severe volume expansion of sulfur during the cycle, and the shuttle effect of the intermediate product lithium polysulfide (LiPSs) have led to low capacity, low safety performance, and poor cycle stability of lithium-sulfur batteries, which have seriously restricted their commercial development.

[0003] At present, the shuttle effect of LiPSs can be effectively slowed down mainly through physical restriction or chemical adsorption of sulfur carriers. However, the shuttle effect is not only due to the dissolution and diffusion of LiPSs, but also the slow conversion reaction kinetics between LiPSs and Li2S2 / Li2S is a very important factor. Therefore, the introduction of catalytic materials that can both properly adsorb LiPSs and achieve rapid conversion of LiPSs, that is, establishing a dynamic balance between the adsorption and smooth conversion of LiPSs, can fundamentally solve the shuttle effect of LiPSs.

[0004] Patent document with application number CN2022117269626 discloses a method for preparing a lithium-sulfur battery catalyst material, which is used to prepare a lithium-sulfur battery catalyst material in which atomically dispersed Ni-Co bimetallic tandem sites are coordinated with nitrogen and embedded in porous carbon. Zn(NO3)2·6H2O, Co(NO3)2·6H2O and Ni(NO3)2·6H2O are dissolved in methanol to form a mixed solution, 2-methylimidazole and methanol are added to the mixed solution and the solution is aged after stirring, and then the precipitate is collected by filtration. The precipitate is washed and vacuum-dried to obtain ZnCoNi-ZIF; the ZnCoNi-ZIF is then placed in a tubular furnace and heated to obtain a pyrolysis product, and the metal particles on the surface of the pyrolysis product are selectively removed after soaking treatment, and then vacuum-dried to obtain a lithium-sulfur battery catalyst material CoNi-NC. The prepared lithium-sulfur battery catalyst material CoNi-NC can be used to prepare a sulfur-based composite material CoNi-NC-S for use as a positive electrode of a lithium-sulfur battery, which can effectively improve the rate performance of the lithium-sulfur battery and has good cycle stability. However, the technical solution of this patent document does not fundamentally solve the shuttle effect of LiPSs.

[0005] Therefore, the present invention applies a catalyst with excellent catalytic activity and low cost to a lithium-sulfur battery, thereby inhibiting the shuttle effect of LiPSs and accelerating the conversion kinetics. There is no relevant report in this regard. Summary of the invention

[0006] The technical problem solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a lithium-sulfur battery catalyst with a simple process and being environmentally friendly. The method utilizes the spatial confinement effect of three-dimensional porous graphene and, based on the ferroelectric piezoelectric effect of Nb-NC during the charge and discharge process, forms a local micro-electric field in situ, accelerates the catalyst to convert soluble LiPSs into insoluble discharge product Li2S, achieves rapid and complete catalytic conversion of LiPSs and significantly improves the rate performance and cycle stability of the lithium-sulfur battery. Therefore, the prepared lithium-sulfur battery catalyst can be used to prepare lithium-sulfur battery positive electrode materials and further assembled into a lithium-sulfur battery.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solution: a preparation method of a lithium-sulfur battery catalyst, the specific preparation steps of which are:

[0008] Step S1: Preparation of three-dimensional porous graphene

[0009] The three-dimensional porous graphene is prepared by a sacrificial aminated silica hard template method, wherein the aminated silica hard template is dispersed in deionized water, and then a graphene oxide solution is added, stirred and mixed evenly, and then allowed to stand, and then washed with water, freeze-dried and microwave-heated to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene, and then treated with a hydrofluoric acid solution to remove the silica hard template, and after the reaction is completed, washed with water and dried to obtain the three-dimensional porous graphene;

[0010] Step S2: Preparation of hollow carbon shell Nb-NC nanocatalysts

[0011] The niobium nitrate and zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is added to the niobium / zinc mixed solution and reacted at 60-80°C, after the reaction is completed, the mixture is centrifuged, washed and dried, and then transferred to a tube furnace for annealing at 900-1100°C for 1-3h and treated with acid to obtain a hollow carbon shell Nb-NC nanocatalyst;

[0012] Step S3: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst

[0013] The nano-In2O3 catalyst and the hollow carbon shell Nb-NC nano-catalyst obtained in step S2 are mixed evenly in anhydrous ethanol, and then the three-dimensional porous graphene obtained in step S1 is added and mixed evenly, and the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst, i.e., a lithium-sulfur battery catalyst, is obtained after heating until the anhydrous ethanol evaporates and drying.

[0014] It is further defined that the specific preparation process of the amino silica hard template described in step S1 is: uniformly dispersing the surfactant hexadecyltrimethylammonium bromide in deionized water; adding NaOH solution under 80~90°C water bath conditions and stirring to mix evenly; then adding tetraethyl silicate and stirring to mix evenly; then adding the coupling agent 3-aminopropyl-trimethoxysilane and stirring to react, cooling to room temperature after the reaction is completed, washing with water and drying to obtain the amino silica hard template.

[0015] It is further defined that the feed ratio of the surfactant hexadecyltrimethylammonium bromide to tetraethyl silicate is 1 g:4~8 mL; the volume ratio of the NaOH solution to tetraethyl silicate is 1:1.5~2, and the concentration of the NaOH solution is 1~3 mol / L; the volume ratio of the coupling agent 3-aminopropyl-trimethoxysilane to tetraethyl silicate is 1:1~1.5.

[0016] It is further defined that the mass ratio of the amino-treated silica hard template to graphene oxide in step S1 is 8-12:1, and the concentration of the graphene oxide solution is 0.1-1 mg / mL.

[0017] It is further defined that the freeze-drying temperature in step S1 is -80~-50°C, the freeze-drying time is 8~48h; the microwave heating power is 350~600W, and the microwave heating time is 2~7min.

[0018] It is further defined that in step S2, the molar ratio of niobium nitrate to zinc nitrate is 1:15-25, and the molar ratio of 2-methylimidazole to the total of niobium nitrate and zinc nitrate is 3-5:1.

[0019] It is further defined that the mass ratio of the nano-In2O3 catalyst to the hollow carbon shell Nb-NC nano-catalyst in step S3 is 1:0.5~2; the mass ratio of the nano-In2O3 catalyst to the porous three-dimensional graphene is 0.5~3:1.

[0020] The application of the lithium-sulfur battery catalyst prepared by the above method in the preparation of lithium-sulfur battery positive electrode materials.

[0021] It is further defined that the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur are evenly mixed in a mass ratio of 3:5~10, and then the mixture is calcined at 150~160°C in an oxygen-free atmosphere for 3~8h to obtain the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S material, which is the positive electrode material of the lithium-sulfur battery.

[0022] Application of the lithium-sulfur battery positive electrode material prepared based on the above method in assembling lithium-sulfur batteries.

[0023] The present invention constructs a lithium-sulfur battery catalyst with "confinement-local micro-electric field assistance-accelerated catalytic conversion" from the perspective of material structure design and multifunctional coupling. First, a three-dimensional porous graphene is constructed by a sacrificial template method, and the shuttle effect of LiPSs is suppressed by virtue of its three-dimensional connected physical confinement effect; then, a hollow carbon shell Nb-NC single atom catalyst with high specific surface area and multi-level pore structure is prepared by a two-step hydrothermal synthesis-pyrolysis method; finally, in order to achieve rapid and complete catalytic conversion of LiPSs, the catalyst In2O3 and the hollow carbon shell Nb-NC single atom catalyst are simultaneously loaded into the three-dimensional porous graphene conductive network. Based on the Nb-NC ferroelectric piezoelectric effect during the charge and discharge process, a local micro-electric field is formed in situ to accelerate the catalyst to convert soluble LiPSs into insoluble discharge product Li2S, fundamentally suppressing the shuttle effect of LiPSs, achieving rapid and complete catalytic conversion of LiPSs and significantly improving its rate performance and cycle stability.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] 1. The reactivity of silanol groups on the surface of nano-SiO2 is very low, and it is difficult to directly carry out grafting modification. Therefore, the present invention adopts a one-step method to add an amino silane coupling agent when tetraethyl silicate is hydrolyzed in an alkaline solution, and the amino coupling agent is used to form a bond between the inorganic and organic interfaces when tetraethyl silicate is hydrolyzed, promoting interface fusion, thereby modifying the surface of SiO2 with amino groups to make it amino.

[0026] 2. The charge effect on graphene oxide mainly comes from the ionization of carboxyl groups, so graphene oxide is a negatively charged particle. The repulsion between negative charges enables graphene oxide to be evenly dispersed in water. The present invention adopts a one-step method to graft amino groups on the surface of the nano-SiO2 hard template to make its surface positively charged. Electrostatic action can be used to combine the amino groups on the surface of the nano-silica template with the carboxyl groups on the graphene oxide. The SiO2 hard template is removed through subsequent acid treatment to form a three-dimensional porous graphene.

[0027] 3. The three-dimensional porous graphene has a large surface area and a high porosity, which can physically limit the shuttle effect of LiPSs and alleviate the volume expansion and poor conductivity of sulfur during the charge and discharge process; in addition, this three-dimensionally connected structure provides a channel for rapid diffusion of ions and electrons, which can achieve rapid charge and discharge performance of electrode materials. At the same time, it also has high porosity, good flexibility and a high specific surface area, providing multiple active sites for the attachment of catalyst In2O3 and hollow carbon shell Nb-NC single atom catalyst. In order to ensure that the pore structure of the three-dimensional porous graphene plays a spatial confinement role on Nb-NC and the selective catalyst In2O3, the particle size of the hollow carbon shell Nb-NC single atom catalyst prepared by the present invention is 100nm, and the catalyst In2O3 uses a commercial particle size of 50nm; at the same time, the particle size of the hard template is controlled to be 200nm.

[0028] 4. Single-atom catalysts have been active in various catalytic fields since they were discovered because of their advantages such as low metal loading, high atomic utilization, high selectivity and catalytic activity. At the same time, as a catalytic material, they also show unique advantages in lithium-sulfur batteries: extremely low metal loading can effectively reduce the mass of the positive electrode and improve the energy density of lithium-sulfur batteries; the introduction of polar sites can improve the adsorption capacity of LiPSs; nearly 100% atomic utilization provides sufficient adsorption sites for LiPSs; unsaturated coordination structure effectively promotes the conversion of LiPSs and accelerates nucleation. The present invention uses a two-step hydrothermal synthesis-pyrolysis method to successfully load Nb single atoms on N-doped carbon. The hollow carbon shell structure of Nb-NC has a high specific surface area and abundant mesopores, which can provide sufficient reaction interface and effectively alleviate the volume expansion of sulfur during the charge and discharge process of lithium-sulfur batteries. N-doped sites and Nb single atoms promote the reversible transformation of Nb-NC to LiPSs by enhancing the polarity of the material. In addition, N-doped carbon improves the conductivity of the material and promotes the electron transfer rate during the charge and discharge process.

[0029] 5. To achieve rapid redox conversion of LiPSs, the designed catalyst should have multiple functions at the same time: strong LiPSs affinity, fast lithium ion / electron diffusion rate and high catalytic activity to achieve rapid redox conversion of LiPSs. (1) In2O3 catalyst with selective catalytic effect reduces the conversion rate of sulfur to soluble LiPSs during discharge; more importantly, the LiInS2 intermediate generated by the reaction can increase the conversion rate of soluble LiPSs to insoluble discharge product LiPSs. This selective catalytic strategy effectively reduces the accumulation of LiPSs in the electrolyte and inhibits the shuttle effect from the source. (2) Nb-based materials have ferroelectric piezoelectric properties. When loaded with external power source for lithium, Nb-NC is polarized due to the ferroelectric effect, so that the dipole moment is aligned and the Nb-NC particles are charged and separated, forming a local micro-electric field. Under the action of the local micro-electric field, Nb-NC and the selective catalyst In2O3 preferentially combine with LiPSs to convert them into insoluble discharge products Li2S, inhibiting the shuttle effect. In addition, during the charge and discharge process, S inevitably produces a huge volume expansion to squeeze Nb-NC. At this time, Nb-NC will further increase the polarization strength due to the piezoelectric effect, thereby accelerating the efficiency of LiPSs conversion. (3) The three-dimensional porous graphene not only improves the conductivity of S and inhibits its expansion, but also plays a role in spatial confinement, thereby deepening the piezoelectric effect of Nb-NC and achieving rapid and continuous conversion of LiPSs. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a SEM image of the hollow carbon shell Nb-NC nanocatalyst obtained in Example 1;

[0031] Figure 2 is the Raman image of the three-dimensional porous graphene obtained in Example 1;

[0032] Figure 3 It is a comparison chart of the rate charge and discharge performance of lithium-sulfur batteries assembled with the positive electrode materials obtained in Examples 1 to 3 and Comparative Examples 1 to 4, respectively. DETAILED DESCRIPTION

[0033] The present invention suppresses the shuttle effect of LiPSs by constructing three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S, solves the problems of sulfur expansion and poor conductivity, and thus improves the electrochemical performance of lithium-sulfur batteries.

[0034] The present invention specifically prepares the positive electrode material of a lithium-sulfur battery by the following method, comprising the following steps:

[0035] (1) Preparation of amino-modified silica hard template

[0036] Disperse the surfactant hexadecyltrimethylammonium bromide (the feed ratio of the surfactant to tetraethyl silicate can be 1g:4~8mL) in deionized water and disperse evenly by ultrasonication; add a NaOH solution with a concentration of 1~3mol / L (the volume ratio of the NaOH solution to tetraethyl silicate can be 1:1.5~2) under water bath conditions, heat the water bath at 80~90℃, and stir for 20~50min; then add tetraethyl silicate and continue stirring for 5~10min; then add the coupling agent 3-aminopropyl-trimethoxysilane (the volume ratio of the coupling agent to tetraethyl silicate can be 1:1~1.5), stir and react for 1~3h, cool to room temperature after the reaction is completed, and then wash and dry to obtain an amino-silica hard template;

[0037] (2) Preparation of graphene oxide solution

[0038] The graphene oxide solution is prepared using the classic "Hummers method for preparing graphene oxide". For example, concentrated sulfuric acid and potassium permanganate are used to treat expanded graphite, and the reaction temperature is controlled in a step-by-step manner during the reaction; the reaction product is washed and dialyzed to obtain a graphene oxide solution of a certain concentration (the concentration of graphene oxide can be selected to be 0.1-1 mg / mL).

[0039] As an example, the present invention is prepared by the following method:

[0040] Under ice bath conditions, add expanded graphite to concentrated sulfuric acid at 0°C and stir evenly; continue to add potassium permanganate under conditions below 10°C; then, under stirring conditions, perform low-temperature reactions at 10-15°C, medium-temperature reactions at 35°C, and high-temperature reactions at 90-95°C in sequence; after the reaction, add distilled water to dilute and add an appropriate amount of hydrogen peroxide until the solution turns bright yellow; let stand, centrifuge to obtain a precipitate, and perform acid washing and distilled water washing; 2- The neutral graphite oxide solution is dialyzed, and after dilution, stirring and ultrasonic treatment, a graphene oxide solution is obtained.

[0041] (3) Preparation of three-dimensional porous graphene

[0042] The three-dimensional porous graphene is prepared by a sacrificial aminated silica hard template method. The aminated silica hard template is dispersed in deionized water and evenly dispersed by ultrasonication. The graphene oxide solution is slowly added (the mass ratio of the aminated silica hard template to the graphene oxide can be 8-12:1), and the mixture is magnetically stirred for 2-4 hours and then allowed to stand for 2-4 hours. After washing with water, the mixture is freeze-dried (the freeze-drying temperature can be -80- -50°C and the freeze-drying time can be 8-48 hours) and microwave heated (the microwave heating power can be 350-600W and the microwave heating time can be 2-7 minutes) to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene. The graphene oxide is then treated with a hydrofluoric acid solution to remove the silica, and after reacting for 2-4 hours, the mixture is washed with water and dried to obtain the three-dimensional porous graphene.

[0043] (4) Preparation of hollow carbon shell Nb-NC nanocatalysts

[0044] Niobium nitrate and zinc nitrate (the molar ratio of niobium nitrate to zinc nitrate can be 1:15-25) are dissolved in methanol to obtain a niobium / zinc mixed solution, 2-methylimidazole (the molar ratio of 2-methylimidazole to (niobium nitrate + zinc nitrate) can be 3-5:1) is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is added to the niobium / zinc mixed solution, reacted at 60-80° C. in a blast oven for 24-36 hours, centrifugally washed and dried, then transferred to a tubular furnace for annealing at 900-1100° C. for 1-3 hours and treated with acid to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0045] (5) Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst

[0046] Selective catalyst nano-In2O3 and three-dimensional porous graphene and hollow carbon shell Nb-NC nano-catalyst are weighed according to a certain mass ratio (the mass ratio of nano-In2O3 to hollow carbon shell Nb-NC can be 1:0.5~2; the mass ratio of nano-In2O3 to porous three-dimensional graphene is 0.5~3:1). Nano-In2O3 and hollow carbon shell Nb-NC are mixed evenly in anhydrous ethanol, and then three-dimensional porous graphene is added and ultrasonicated for 1~2h, and then heated until the anhydrous ethanol is volatilized, and three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst is obtained after drying.

[0047] (6) Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S cathode material

[0048] The three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur are evenly mixed in a mass ratio of 3:5~10, and then transferred to a tubular furnace and calcined (calcination temperature can be 150~160℃, calcination time can be 3~8h) in an oxygen-free atmosphere (nitrogen protection can be optional) to obtain a three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material.

[0049] The catalyst prepared by the above method can be further applied to lithium-sulfur batteries, specifically, it can be used as a battery positive electrode material for assembling lithium-sulfur batteries.

[0050] In order to better illustrate the above technical solution, the above technical solution will be described in detail below in conjunction with specific embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies implemented based on the above content of the present invention belong to the scope of the present invention. Example 1

[0051] Step S1: Preparation of an amino-silica hard template: 0.4 g of surfactant hexadecyltrimethylammonium bromide was dispersed in an appropriate amount of deionized water, and ultrasonically dispersed; 1.4 mL of a 2 mol / L NaOH solution was added in a water bath; the mixture was heated to 85° C. in a water bath, stirred for 30 min, and then 2.4 mL of tetraethyl silicate was added, and stirring was continued for 7 min, and then 2 mL of a coupling agent 3-aminopropyl-trimethoxysilane was added, and stirring was continued for 2 h, and the mixture was cooled to room temperature; the amino-silica hard template was obtained by washing with water and drying;

[0052] Step S2: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring and add distilled water (about 50mL) dropwise, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker, dilute it to 800mL with distilled water, add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow, let it stand until the precipitation is complete, and pour out the supernatant. Centrifuge the precipitate and pickle it with 5wt% hydrochloric acid in a centrifuge tube until there is no SO4 in the supernatant. 2-(Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted to a certain volume with distilled water and stirred for 1 hour, then ultrasonically treated for 1 hour and measured by constant weight method to find its concentration to be 0.5 mg / mL.

[0053] Step S3: Preparation of three-dimensional porous graphene: Three-dimensional porous graphene is prepared by sacrificial amino-silica hard template method. Disperse 750mg of amino-silica hard template in step S1 in an appropriate amount of deionized water, and disperse evenly by ultrasonication; slowly add 150mL of 0.5mg / mL graphene oxide solution in step S2, stir magnetically for 3h and then stand for 3h; wash with water and freeze-dry at -70℃ for 24h; then microwave heat treatment at 450W power for 4min to reduce carbonyl, carboxyl and other groups in graphene oxide to generate graphene; then treat with hydrofluoric acid solution to remove silica, and after reacting for 3h, wash with water and dry to obtain three-dimensional porous graphene.

[0054] Step S4: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 4 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 16.8 mol 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is poured into the niobium / zinc mixed solution, and the mixture is reacted at 70° C. in a blast oven for 30 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 1000° C. for 1.5 h and acid-treated to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0055] Step S5: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst: 0.1g nano-In2O3 and 0.1g hollow carbon shell Nb-NC in step S4 were mixed evenly in anhydrous ethanol, 0.15g three-dimensional porous graphene was immersed in the solution of the evenly mixed In2O3 and hollow carbon shell Nb-NC, and then ultrasonicated for 1.5h and heated until the anhydrous ethanol evaporated, and the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst was obtained after drying.

[0056] Step S6: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material: The three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S5 are mixed evenly in a mass ratio of 3:7, and then transferred to a tubular furnace, and calcined at 155°C for 6 hours under nitrogen protection to obtain a three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material. Example 2

[0057] Step S1: Preparation of an amino-silica hard template: 0.4 g of surfactant hexadecyltrimethylammonium bromide was dispersed in an appropriate amount of deionized water, and ultrasonically dispersed; 1.07 mL of a 1 mol / L NaOH solution was added in a water bath; the mixture was heated to 80° C. in a water bath, stirred for 20 min, and then 1.6 mL of tetraethyl silicate was added, and stirring was continued for 5 min, and then 1.6 mL of a coupling agent 3-aminopropyl-trimethoxysilane was added, and stirring was continued for 1 h, and the mixture was cooled to room temperature; the amino-silica hard template was obtained by washing with water and drying;

[0058] Step S2: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring and add distilled water (about 50mL) dropwise, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker and dilute it to 800mL with distilled water. Add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow, let it stand until the precipitation is complete, and pour off the supernatant. Centrifuge the precipitate and pickle it with 5wt% hydrochloric acid in a centrifuge tube until there is no SO4 in the supernatant. 2- (Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted to a certain volume with distilled water and stirred for 1 hour, then ultrasonically treated for 1 hour and measured its concentration by constant weight method to be 0.1 mg / mL.

[0059] Step S3: Preparation of three-dimensional porous graphene: Three-dimensional porous graphene is prepared by sacrificial amino-silica hard template method. Disperse 120 mg of amino-silica hard template in step S1 in an appropriate amount of deionized water, and disperse evenly by ultrasonication; slowly add 150 mL of 0.1 mg / mL graphene oxide solution in step S2, stir magnetically for 2 hours, and then stand for 2 hours; wash with water and freeze-dry at -80°C for 8 hours; then microwave heat treatment at 350W power for 2 minutes to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene; then treat with hydrofluoric acid solution to remove silica, and after reacting for 2 hours, wash with water and dry to obtain three-dimensional porous graphene.

[0060] Step S4: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 3 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 9.6 mol 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is poured into the niobium / zinc mixed solution, and the mixture is reacted at 60° C. in a blast oven for 24 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 900° C. for 1 h and acid-treated to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0061] Step S5: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst: 0.1g nano-In2O3 and 0.05g hollow carbon shell Nb-NC in step S4 were mixed evenly in anhydrous ethanol, 0.2g three-dimensional porous graphene was immersed in the solution of the evenly mixed In2O3 and hollow carbon shell Nb-NC, and then ultrasonicated for 1h and heated until the anhydrous ethanol evaporated, and the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst was obtained after drying.

[0062] Step S6: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material: The three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S5 are mixed evenly in a mass ratio of 3:5, and then transferred to a tubular furnace, and calcined at 150°C for 3 hours under nitrogen protection to obtain a three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material. Example 3

[0063] Step S1: Preparation of an amino-silica hard template: 0.4 g of surfactant hexadecyltrimethylammonium bromide was dispersed in an appropriate amount of deionized water, and ultrasonically dispersed; 1.6 mL of a 3 mol / L NaOH solution was added in a water bath; the mixture was heated to 90° C. in a water bath, stirred for 50 min, and then 3.2 mL of tetraethyl silicate was added, and stirring was continued for 10 min, and then 2.13 mL of a coupling agent 3-aminopropyl-trimethoxysilane was added, and stirring was continued for 3 h, and the mixture was cooled to room temperature; the amino-silica hard template was obtained by washing with water and drying;

[0064] Step S2: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C, and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring, and add distilled water (about 50mL) drop by drop, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker and dilute it to 800mL with distilled water. Add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow. Let it stand until the precipitation is complete and pour out the supernatant. The precipitate was centrifuged and washed with 5wt% hydrochloric acid in a centrifuge tube until there was no SO4 in the supernatant. 2- (Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The above graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted with distilled water to a certain volume, stirred for 1 hour, and then ultrasonically treated for 1 hour. The concentration was measured by constant weight method to be 1 mg / mL.

[0065] Step S3: Preparation of three-dimensional porous graphene: Three-dimensional porous graphene is prepared by sacrificial amino-silica hard template method. Disperse 1800 mg of amino-silica hard template in step S1 in an appropriate amount of deionized water, and disperse evenly by ultrasonication; slowly add 150 mL of 1 mg / mL graphene oxide solution in step S2, stir magnetically for 4 hours, and then stand for 4 hours; after washing with water, freeze-dry at -50°C for 48 hours; then heat with microwave at 600W for 7 minutes to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene; remove silica by treatment with hydrofluoric acid solution, and after reacting for 4 hours, wash with water and dry to obtain three-dimensional porous graphene.

[0066] Step S4: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 5 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 26 mol 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is added to the niobium / zinc mixed solution, and the mixture is reacted at 80° C. in a blast oven for 36 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 1100° C. for 3 h and acid-treated to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0067] Step S5: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst: 0.1g nano-In2O3 and 0.2g hollow carbon shell Nb-NC in step S4 were mixed evenly in anhydrous ethanol, 0.033g three-dimensional porous graphene was immersed in the solution of the evenly mixed In2O3 and hollow carbon shell Nb-NC, and then ultrasonicated for 2h and heated until the anhydrous ethanol evaporated, and the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst was obtained after drying.

[0068] Step S6: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material: The three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S5 are mixed evenly in a mass ratio of 3:10, and then transferred to a tubular furnace, and calcined at 160°C for 8 hours under nitrogen protection to obtain a three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material.

[0069] Comparative Example 1 (using only ordinary graphene without using amino-treated silica hard template)

[0070] Step S1: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring and add distilled water (about 50mL) dropwise, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker, dilute it to 800mL with distilled water, add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow, let it stand until the precipitation is complete, and pour out the supernatant. Centrifuge the precipitate and pickle it with 5wt% hydrochloric acid in a centrifuge tube until there is no SO4 in the supernatant. 2- (Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted to a certain volume with distilled water and stirred for 1 hour, then ultrasonically treated for 1 hour and measured by constant weight method to find its concentration to be 0.5 mg / mL.

[0071] Step S2: 150 mL of the 0.5 mg / mL graphene oxide solution in step S1 is magnetically stirred for 3 hours and then allowed to stand for 3 hours; after washing with water, it is freeze-dried at -70°C for 24 hours; and then subjected to microwave heating at 450 W for 4 minutes to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene.

[0072] Step S3: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 4 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 16.8 mol 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is added to the niobium / zinc mixed solution, and the mixture is reacted at 70° C. in a blast oven for 30 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 1000° C. for 1.5 h and treated with acid to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0073] Step S4: Preparation of graphene@In2O3@hollow carbon shell Nb-NC catalyst: 0.1g nano-In2O3 and 0.1g hollow carbon shell Nb-NC in step S3 were mixed evenly in anhydrous ethanol, 0.15g graphene was immersed in the solution of the evenly mixed In2O3 and hollow carbon shell Nb-NC, and after ultrasonic treatment for 1.5h, the mixture was heated until the anhydrous ethanol was volatilized, and the graphene@In2O3@hollow carbon shell Nb-NC catalyst was obtained after drying.

[0074] Step S5: Preparation of graphene@In2O3@hollow carbon shell Nb-NC@S: The graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S4 are mixed evenly in a mass ratio of 3:7, then transferred to a tubular furnace, and calcined at 155°C for 6 hours under nitrogen protection to obtain the graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material.

[0075] Comparative Example 2 (without addition of hollow carbon shell Nb-NC nanocatalyst)

[0076] Step S1: Preparation of an amino-silica hard template: 0.4 g of surfactant hexadecyltrimethylammonium bromide was dispersed in an appropriate amount of deionized water, and ultrasonically dispersed; 1.4 mL of a 2 mol / L NaOH solution was added in a water bath; the mixture was heated to 85° C. in a water bath, stirred for 30 min, and then 2.4 mL of tetraethyl silicate was added, and stirring was continued for 7 min, and then 2 mL of a coupling agent 3-aminopropyl-trimethoxysilane was added, and stirring was continued for 2 h, and the mixture was cooled to room temperature; the amino-silica hard template was obtained by washing with water and drying;

[0077] Step S2: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring and add distilled water (about 50mL) dropwise, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker, dilute it to 800mL with distilled water, add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow, let it stand until the precipitation is complete, and pour out the supernatant. Centrifuge the precipitate and pickle it with 5wt% hydrochloric acid in a centrifuge tube until there is no SO4 in the supernatant. 2- (Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted to a certain volume with distilled water and stirred for 1 hour, then ultrasonically treated for 1 hour and measured by constant weight method to find its concentration to be 0.5 mg / mL.

[0078] Step S3: Preparation of three-dimensional porous graphene: Three-dimensional porous graphene is prepared by sacrificial amino-silica hard template method. Disperse 750mg of amino-silica hard template in step S1 in an appropriate amount of deionized water, and disperse evenly by ultrasonication; slowly add 150mL of 0.5mg / mL graphene oxide solution in step S2, stir magnetically for 3h and then stand for 3h; after washing with water, freeze-dry at -70℃ for 24h; then microwave heating at 450W power for 4min to reduce carbonyl and carboxyl groups in graphene oxide to generate graphene; remove silica by hydrofluoric acid solution treatment, and after reacting for 3h, wash with water and dry to obtain three-dimensional porous graphene.

[0079] Step S4: Preparation of three-dimensional porous graphene @ In2O3 catalyst: 0.1 g of nano-In2O3 was mixed evenly in anhydrous ethanol, 0.15 g of three-dimensional porous graphene was immersed in the evenly mixed In2O3 solution, ultrasonicated for 1.5 h, and then heated until the anhydrous ethanol evaporated, and dried to obtain a three-dimensional porous graphene @ In2O3 catalyst.

[0080] Step S5: Preparation of three-dimensional porous graphene @ In2O3 @ S: The three-dimensional porous graphene @ In2O3 catalyst and elemental sulfur in step S4 are mixed evenly in a mass ratio of 3:7, then transferred to a tubular furnace, and calcined at 155 ° C for 6 hours under nitrogen protection to obtain a three-dimensional porous graphene @ In2O3 @ S positive electrode material.

[0081] Comparative Example 3 (without adding selective catalyst In2O3)

[0082] Step S1: Preparation of an amino-silica hard template: 0.4 g of surfactant hexadecyltrimethylammonium bromide was dispersed in an appropriate amount of deionized water, and ultrasonically dispersed; 1.4 mL of a 2 mol / L NaOH solution was added in a water bath; the mixture was heated to 85° C. in a water bath, stirred for 30 min, and then 2.4 mL of tetraethyl silicate was added, and stirring was continued for 7 min, and then 2 mL of a coupling agent 3-aminopropyl-trimethoxysilane was added, and stirring was continued for 2 h, and the mixture was cooled to room temperature; the amino-silica hard template was obtained by washing with water and drying;

[0083] Step S2: Preparation of graphene oxide solution: Add 46mL of concentrated sulfuric acid to a 250mL dry beaker and stir magnetically under ice bath conditions. When the temperature reaches 0°C, slowly add 2g of expanded graphite, and after stirring evenly, continue to slowly add 6g of potassium permanganate (keep the temperature below 10°C). Take out some ice cubes, keep the temperature at 10~15°C and continue stirring for 2h (low temperature reaction). Then place the beaker in a constant temperature water bath at 35°C and continue stirring for 30min (medium temperature reaction). Finally, transfer the beaker to a 90°C water bath, keep stirring and add distilled water (about 50mL) dropwise, strictly controlling it below 95°C (high temperature reaction). After the reaction is completed, transfer the solution to a 1000mL beaker, dilute it to 800mL with distilled water, add an appropriate amount of 5wt% hydrogen peroxide until the solution is bright yellow, let it stand until the precipitation is complete, and pour out the supernatant. Centrifuge the precipitate and pickle it with 5wt% hydrochloric acid in a centrifuge tube until there is no SO4 in the supernatant. 2- (Tested with 5wt% BaCl2) and then washed with distilled water until the supernatant was neutral (tested with pH paper) to obtain a graphite oxide solution. The graphite oxide solution was placed in a dialysis bag and dialyzed for one week. Diluted to a certain volume with distilled water and stirred for 1 hour, then ultrasonically treated for 1 hour and measured by constant weight method to find its concentration to be 0.5 mg / mL.

[0084] Step S3: Preparation of three-dimensional porous graphene: Three-dimensional porous graphene is prepared by sacrificial amino-silica hard template method. Disperse 750mg of amino-silica hard template in step S1 in an appropriate amount of deionized water, and disperse evenly by ultrasonication; slowly add 150mL of 0.5mg / mL graphene oxide solution in step S2, stir magnetically for 3h and then stand for 3h; after washing with water, freeze-dry at -70℃ for 24h; then microwave heating at 450W power for 4min to reduce carbonyl and carboxyl groups in graphene oxide to generate graphene; remove silica by hydrofluoric acid solution treatment, and after reacting for 3h, wash with water and dry to obtain three-dimensional porous graphene.

[0085] Step S4: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 4 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 16.8 mol 2-methylimidazole is dissolved in methanol to obtain 2-methylimidazole, the 2-methylimidazole solution is added to the niobium / zinc mixed solution, and the mixture is reacted at 70° C. in a blast oven for 30 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 1000° C. for 1.5 h and acid-treated to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0086] Step S5: Preparation of three-dimensional porous graphene@hollow carbon shell Nb-NC catalyst: 0.1 g of hollow carbon shell Nb-NC in step S4 was mixed evenly in anhydrous ethanol, 0.15 g of three-dimensional porous graphene was immersed in the evenly mixed hollow carbon shell Nb-NC solution, and then ultrasonicated for 1.5 h and heated until the anhydrous ethanol evaporated, and dried to obtain a three-dimensional porous graphene@hollow carbon shell Nb-NC catalyst.

[0087] Step S6: Preparation of three-dimensional porous graphene@hollow carbon shell Nb-NC@S positive electrode material: The three-dimensional porous graphene@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S5 are mixed evenly in a mass ratio of 3:7, and then transferred to a tubular furnace, and calcined at 155°C for 6 hours under nitrogen protection to obtain a three-dimensional porous graphene@hollow carbon shell Nb-NC@S positive electrode material.

[0088] Comparative Example 4 (no three-dimensional porous graphene added)

[0089] Step S1: Preparation of hollow carbon shell Nb-NC nanocatalyst: 0.2 mol niobium nitrate and 4 mol zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 16.8 mol 2-methylimidazole is dissolved in methanol to obtain 2-methylimidazole, the 2-methylimidazole solution is added to the niobium / zinc mixed solution, and the mixture is reacted at 70° C. in a blast oven for 30 h, and then centrifugally washed and dried, and then transferred to a tubular furnace for annealing at 1000° C. for 1.5 h and acid-treated to obtain a hollow carbon shell Nb-NC nanocatalyst.

[0090] Step S2: Preparation of In2O3@hollow carbon shell Nb-NC catalyst: 0.1 g of nano-In2O3 and 0.1 g of hollow carbon shell Nb-NC in step S1 were mixed evenly in anhydrous ethanol, ultrasonicated for 1.5 h and then heated until the anhydrous ethanol evaporated, and then dried to obtain the In2O3@hollow carbon shell Nb-NC catalyst.

[0091] Step S3: Preparation of In2O3@hollow carbon shell Nb-NC@S positive electrode material: The In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in step S2 are mixed evenly in a mass ratio of 3:7, and then transferred to a tubular furnace, and calcined at 155°C for 6 hours under nitrogen protection to obtain In2O3@hollow carbon shell Nb-NC@S positive electrode material.

[0092] Product performance test:

[0093] Before the electrochemical test, the electrodes are prepared and button cells are assembled, and then the battery electrical performance is tested using a charge and discharge test cabinet.

[0094] from Figure 1 It can be seen from the SEM results that the hollow carbon shell Nb-NC single atom catalysts synthesized according to the method of Example 1 all present a dodecahedral structure with clear edges and corners.

[0095] from Figure 2 It can be seen from the Raman results that the three-dimensional porous graphene synthesized according to the method of Example 1 exhibits typical Raman characteristic peaks of carbon materials. -1 The D peak at 1582cm -1 The G peak of the D peak represents the defect degree of the material, and the G peak represents the graphitization degree of the material. The intensity ratio of the D peak to the G peak (ID / IG) reflects the disorder degree of the material. Raman testing found that the three-dimensional porous graphene synthesized by the present invention has a lower degree of graphitization and a higher degree of defects.

[0096] from Figure 3 It can be seen from the electrical performance test results that the lithium-sulfur battery assembled with the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S positive electrode material prepared in Example 1 of the present invention has better rate performance and capacity recovery performance.

[0097] Based on the above test results, it can be seen that the present invention can achieve the regulation of the microstructure properties of the positive electrode material of the lithium-sulfur battery through the construction of three-dimensional porous graphene, the construction of hollow carbon shell Nb-NC single atom catalyst, and the simultaneous loading of catalyst In2O3 and hollow carbon shell Nb-NC single atom catalyst. The catalyst of the lithium-sulfur battery is uniquely "confined-local micro-electric field assisted-accelerated catalytic conversion", which effectively inhibits the shuttle effect of LiPSs. The design of the three-dimensional porous graphene @ In2O3 @ hollow carbon shell Nb-NC @ S catalytic material constructed in Example 1 of the present invention realizes the coupling effect of different functions. This structure not only solves the problem of poor sulfur conductivity, but also effectively inhibits the shuttle effect of LiPSs, and achieves a comprehensive improvement in high-rate charge and discharge performance and cycle stability. However, the use of a single material structure or the lack of a certain material structure (Comparative Examples 1-4) cannot solve the shuttle effect of LiPSs and the improvement of electrochemical performance, and the improper use of certain key parameters in the preparation process (Examples 2-3) makes the catalyst unable to achieve the optimal use effect.

[0098] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium-sulfur battery catalyst, characterized in that The specific preparation steps are: Step S1: Preparation of three-dimensional porous graphene The three-dimensional porous graphene is prepared by a sacrificial aminated silica hard template method, wherein the aminated silica hard template is dispersed in deionized water, and then a graphene oxide solution is added, stirred and mixed evenly, and then allowed to stand, and then washed with water, freeze-dried and microwave-heated to reduce the carbonyl and carboxyl groups in the graphene oxide to generate graphene, and then treated with a hydrofluoric acid solution to remove the silica hard template, and after the reaction is completed, washed with water and dried to obtain the three-dimensional porous graphene; Step S2: Preparation of hollow carbon shell Nb-NC nanocatalysts The niobium nitrate and zinc nitrate are dissolved in methanol to obtain a niobium / zinc mixed solution, 2-methylimidazole is dissolved in methanol to obtain a 2-methylimidazole solution, the 2-methylimidazole solution is added to the niobium / zinc mixed solution and reacted at 60-80°C, after the reaction is completed, the mixture is centrifuged, washed and dried, and then transferred to a tube furnace for annealing at 900-1100°C for 1-3h and treated with acid to obtain a hollow carbon shell Nb-NC nanocatalyst; Step S3: Preparation of three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst The nano-In2O3 catalyst and the hollow carbon shell Nb-NC nano-catalyst obtained in step S2 are mixed evenly in anhydrous ethanol, and then the three-dimensional porous graphene obtained in step S1 is added and mixed evenly, and the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst is obtained after heating until the anhydrous ethanol evaporates and drying.

2. The method for preparing a lithium-sulfur battery catalyst according to claim 1, characterized in that: The specific preparation process of the amino silica hard template described in step S1 is: uniformly dispersing the surfactant hexadecyltrimethylammonium bromide in deionized water; adding NaOH solution under 80~90℃ water bath conditions and stirring and mixing evenly; then adding tetraethyl silicate and stirring and mixing evenly; then adding coupling agent 3-aminopropyl-trimethoxysilane and stirring for reaction, cooling to room temperature after the reaction is completed, washing with water and drying to obtain the amino silica hard template.

3. The method for preparing a lithium-sulfur battery catalyst according to claim 2, characterized in that: The feed ratio of the surfactant hexadecyltrimethylammonium bromide to tetraethyl silicate is 1g:4-8mL; the volume ratio of the NaOH solution to tetraethyl silicate is 1:1.5-2, and the concentration of the NaOH solution is 1-3mol / L; the volume ratio of the coupling agent 3-aminopropyl-trimethoxysilane to tetraethyl silicate is 1:1-1.

5.

4. The method for preparing a lithium-sulfur battery catalyst according to claim 1, characterized in that: The mass ratio of the amino-treated silica hard template to graphene oxide in step S1 is 8-12:1, and the concentration of the graphene oxide solution is 0.1-1 mg / mL.

5. The method for preparing a lithium-sulfur battery catalyst according to claim 1, characterized in that: In step S1, the freeze drying temperature is -80 to -50°C, the freeze drying time is 8 to 48 hours, the microwave heating power is 350 to 600 W, and the microwave heating time is 2 to 7 minutes.

6. The method for preparing a lithium-sulfur battery catalyst according to claim 1, characterized in that: In step S2, the molar ratio of niobium nitrate to zinc nitrate is 1:15-25, and the molar ratio of 2-methylimidazole to the total of niobium nitrate and zinc nitrate is 3-5:

1.

7. The method for preparing a lithium-sulfur battery catalyst according to claim 1, characterized in that: The mass ratio of the nano-In2O3 catalyst to the hollow carbon shell Nb-NC nano-catalyst in step S3 is 1:0.5~2; the mass ratio of the nano-In2O3 catalyst to the porous three-dimensional graphene is 0.5~3:

1.

8. Use of the lithium-sulfur battery catalyst prepared according to the method described in any one of claims 1 to 7 in the preparation of lithium-sulfur battery positive electrode materials.

9. The use according to claim 8, characterized in that The specific process is: mix the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC catalyst and elemental sulfur in a mass ratio of 3:5~10, and then calcine the mixture at 150~160℃ for 3~8h in an oxygen-free atmosphere to obtain the three-dimensional porous graphene@In2O3@hollow carbon shell Nb-NC@S material, which is the positive electrode material of lithium-sulfur battery.

10. The use according to claim 9, characterized in that: The lithium-sulfur battery positive electrode material is used for assembling a lithium-sulfur battery.

Citation Information

Patent Citations

  • Lithium-sulfur battery composite positive electrode material and preparation method thereof

    CN106532016A

  • Preparation method and application of porous lithium-sulfur battery composite material rich in carbon and cobalt sulfide defects

    CN118825244A